Ownership Structure and Inventory Method Choice - Niehaus, Gregory R. (The Accounting Review, 1989)
[This paper examines the relation between inventory method choice and both managerial ownership and outside ownership concentration. It is hypothesized that a conflict of interest between managers and shareholders can arise over inventory method choice, and that ownership structure, in part, determines how potential conflicts of interest are resolved. The evidence is consistent with this hypothesis as the inventory choice appears to be related to both managerial ownership and outside ownership concentration. When managerial ownership is low, the likelihood of LIFO is negatively related to managerial ownership. However, when managerial ownership is high, the likelihood of LIFO is positively related to managerial ownership. Higher outside ownership concentration appears to increase the likelihood of LIFO, ceteris paribus.]